2010
DOI: 10.1177/1524839910382624
|View full text |Cite
|
Sign up to set email alerts
|

Using Intervention Mapping to Promote the Receipt of Clinical Preventive Services Among Women With Physical Disabilities

Abstract: This article describes the development of Promoting Access to Health Services (PATHS), an intervention to promote regular use of clinical preventive services by women with physical disabilities. The intervention was developed using intervention mapping (IM), a theory-based logical process that incorporates the six steps of assessment of need, preparation of matrices, selection of theoretical methods and strategies, program design, program implementation, and evaluation. The development process used methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Gans and colleagues emphasized that developing a culturally sensitive successful program requires dedication of adequate time and other resources by researchers for the formative stage [ 47 ]. Similarly, Suzuki and colleagues also found the application of IM to be complex and time intensive; none the less, they concluded that “the final program product was relevant and useful to its participants, and the extensive planning and assessment largely determined that success” [ 49 ]. In the formative study, we employed the use of a self –administered questionnaire to assess the perceptions of health care providers about involving CHWs in the management of childhood fevers.…”
Section: Discussionmentioning
confidence: 99%
“…Gans and colleagues emphasized that developing a culturally sensitive successful program requires dedication of adequate time and other resources by researchers for the formative stage [ 47 ]. Similarly, Suzuki and colleagues also found the application of IM to be complex and time intensive; none the less, they concluded that “the final program product was relevant and useful to its participants, and the extensive planning and assessment largely determined that success” [ 49 ]. In the formative study, we employed the use of a self –administered questionnaire to assess the perceptions of health care providers about involving CHWs in the management of childhood fevers.…”
Section: Discussionmentioning
confidence: 99%
“…Il a été utilisé dans cet objectif parmi diverses populations défavorisées [44,[83][84][85][86][87].…”
Section: Intérêts Du Protocoleunclassified
“…8 We followed methods consistent with published guidelines for health promotion interventions for people with disabilities 9 during intervention development (described elsewhere). 10 The resulting program is a 90-to 120-minute participatory small-group workshop (mean of four participants per workshop) and structured telephone support for 6 months (with five monthly calls attempted, and a mean of 2.3 calls with structured support completed per participant during the study). Both of these intervention components were led by women with mobility disabilities.…”
Section: Interventionmentioning
confidence: 99%